(untitled) (Research, Society and Development, 2020)
Objective: to promote reflection on the skills of nurses in the field of dermatology. Method: it is a theoretical reflection based on a bibliographic research for theoretical foundation. Result: In the multifaceted reality of daily nursing, nurses are agents of the health work process, with general training. One of the challenges has been to face a diversity of situations that are not always able to intervene resolutely, a reality that leads the category to face ethical and moral dilemmas. In this context, it is highlighted that dermatological diseases are among the three main demands for seeking health services, requiring nurses to have skills in prevention, treatment and recovery. Another aspect that affects the quality of care for this specific clientele is related to the training of specialists in dermatology, since the syllabus of the courses focus on topics related to the treatment of wounds, neglecting the care of people with skin disorders, a fact that makes assistance difficult. dignified and risk-free to this specific clientele. Conclusion: In order to guarantee the quality of skin care, it is necessary for the professional nurse to have a set of knowledge, skills and abilities for adequate preparation of the environment, comprehensive assessment of the person; consistent selection of resources and products; implementation of protocols and guides, in addition to conducting research with significant levels of evidence among this specific clientele. It is believed to be essential to establish the skills and abilities of the specialist nurse in dermatology in Brazil so that training programs can align with the defined proposals.